Analisis Kebutuhan Bahan Ajar untuk Mata Kuliah Sosiologi Ekonomi pada Program Studi Pendidikan Ekonomi Universitas Pamulang - Syafaatul Hidayati; Ahmad Hidayat; Arip Rahman (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2026)
This study aims to analyze students' needs for the development of teaching materials for the Economic Sociology course in the Economic Education Study Program. A quantitative descriptive method with a survey approach was employed, involving 63 students as respondents. The findings indicate that most students consider the course important (95.3%) and relevant to contemporary socio-economic issues (90.4%). However, 34.9% of the students still experience difficulties in understanding abstract concepts, while 47.6% encounter challenges in obtaining supporting references. In addition, 79.4% of the respondents expect teaching materials that are more systematic, written in clear and simple language (95.3%), and available in an easily accessible digital format (77.8%). Based on these findings, the study recommends the development of an interactive e-book incorporating case studies, visual illustrations, self-assessment exercises, and project-based learning activities.